A FSM based Framework to improve Online Shopping System - N. Jayakanthan (International Journal of Advanced Science and Technology, 2020)
Online shopping is major trend in commerce now. People are addicted to buy things in online. But when the number of customers are increased drastically the online system facing a performance degradation. The decrease in the rate of response errors in order processing are the challenges. Hence a mode FlexShop is propose to address the above mentioned issues. FSM algorithm is used in this proposed model to find the scheduled to order fulfillment, This approach address the performance issues.